2021
DOI: 10.1016/j.onehlt.2021.100360
|View full text |Cite
|
Sign up to set email alerts
|

Meta-transcriptomic analysis of the virome and microbiome of the invasive Indian myna (Acridotheres tristis) in Australia

Abstract: Invasive species exert a serious impact on native fauna and flora and have become the target of eradication and management efforts worldwide. Invasive avian species can also be important pathogen reservoirs, although their viromes and microbiomes have rarely been studied. As one of the top 100 invasive pest species globally, the expansion of Indian mynas ( Acridotheres tristis ) into peri-urban and rural environments, in conjunction with increasing free-ranging avian agricultural practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…However, recent studies have also identified hepatoviruses in birds [48,57], and our phylogenetic analysis suggests that the avian viruses sit basal to those viruses found in small mammals, both with midpoint rooting and using the closely related genus Tremovirus as an outgroup. This phylogenetic pattern suggests that birds, rather than mammals, may .…”
Section: Discussionmentioning
confidence: 56%
“…However, recent studies have also identified hepatoviruses in birds [48,57], and our phylogenetic analysis suggests that the avian viruses sit basal to those viruses found in small mammals, both with midpoint rooting and using the closely related genus Tremovirus as an outgroup. This phylogenetic pattern suggests that birds, rather than mammals, may .…”
Section: Discussionmentioning
confidence: 56%
“…We also identified a novel siadenovirus in the Eurasian blackbird library, most closely related to myna siadenovirus found in Australia [59]. Recent studies have identified siadenoviruses in multiple passerine species both in the wild and in captivity, including finches, silvereyes, and mynas [59][60][61]. To our knowledge, this is the first siadenovirus identified in a Eurasian blackbird, and the first siadenovirus identified in New Zealand.…”
Section: Discussionmentioning
confidence: 61%
“…We also identified a novel siadenovirus in the Eurasian blackbird library, most closely related to myna siadenovirus found in Australia [59]. Recent studies have identified siadenoviruses in multiple passerine species both in the wild and in captivity, including finches, silvereyes, and mynas [59-61].…”
Section: Discussionmentioning
confidence: 98%
“…We also identified a novel siadenovirus in the Eurasian blackbird library, most closely related to myna siadenovirus found in Australia [ 61 ]. Recent studies have identified siadenoviruses in multiple passerine species both in the wild and in captivity, including finches, silvereyes, and mynas [ 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also identified a novel siadenovirus in the Eurasian blackbird library, most closely related to myna siadenovirus found in Australia [ 61 ]. Recent studies have identified siadenoviruses in multiple passerine species both in the wild and in captivity, including finches, silvereyes, and mynas [ 61 , 62 , 63 ]. To our knowledge, this is the first siadenovirus identified in a Eurasian blackbird, and the first siadenovirus identified in New Zealand.…”
Section: Discussionmentioning
confidence: 99%